The implications of evaluation and educational policy reforms on English secondary school music education. Issue 3 (3rd July 2019) - Fautley, Martin
Abstract: Neoliberalism in government thought and action has taken a very specific route in England. Building on a policy research grounding, and subjecting governmental and ministerial utterances to careful consideration, this article discusses the ways in which the specifically English situation has evolved. It reports that government has been carefully manipulative in terms of meeting its objectives and of finding ways in which to privilege science, technology, engineering, and math subjects in the curriculum of schools, while at the same time downplaying the place and role of the arts. It describes how school performance measures, the English Baccalaureate and Progress 8, are utilized to achieve the desired ends. The means by which governmental policies find their outworkings in the day-to-day lived experiences of schools are discussed, and the pernicious effects of these policies on the operationalizing of arts curricula generally, and music education in particular, are instantiated and discussed.